2020
DOI: 10.1038/s41467-020-15152-9
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate nanoclay edge-site interactions facilitate hydrogel self-assembly and sustained growth factor localization

Abstract: Nanoclays have generated interest in biomaterial design for their ability to enhance the mechanics of polymeric materials and impart biological function. As well as their utility as physical cross-linkers, clays have been explored for sustained localization of biomolecules to promote in vivo tissue regeneration. To date, both biomolecule-clay and polymer-clay nanocomposite strategies have utilised the negatively charged clay particle surface. As such, biomolecule-clay and polymer-clay interactions are set in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 27 publications
2
61
0
Order By: Relevance
“…For example, the ability of clay to take up and bind bioactive molecules has been used to initiate the formation of new vessels in a wound with the help of vascular endothelial growth factor localization and to stimulate osteogenesis at notably reduced bone morphogenetic protein (BMP) doses ( Gibbs et al., 2016 ). Another example showed that stable Laponite@BMP-2 complexes can be formed by the strong static binding between Laponite nanoplatelets and BMP-2 to effectively preserve the intrinsic bioactivity of BMP-2 and prolong the release period ( Kim et al., 2020 ; Zhang et al., 2020 ).
Figure 2 Possible Models Illustrating How Clay May Promote Osteogenesis (A) Ionic dissolution behavior of Laponite inside cells, and the subsequent enhancement in the intracellular concentration of ions and minerals such as lithium, magnesium, and silicate and all degradation products that are known to affect osteogenic cell function.
…”
Section: Classification Of Nanocomposite Hydrogelsmentioning
confidence: 99%
“…For example, the ability of clay to take up and bind bioactive molecules has been used to initiate the formation of new vessels in a wound with the help of vascular endothelial growth factor localization and to stimulate osteogenesis at notably reduced bone morphogenetic protein (BMP) doses ( Gibbs et al., 2016 ). Another example showed that stable Laponite@BMP-2 complexes can be formed by the strong static binding between Laponite nanoplatelets and BMP-2 to effectively preserve the intrinsic bioactivity of BMP-2 and prolong the release period ( Kim et al., 2020 ; Zhang et al., 2020 ).
Figure 2 Possible Models Illustrating How Clay May Promote Osteogenesis (A) Ionic dissolution behavior of Laponite inside cells, and the subsequent enhancement in the intracellular concentration of ions and minerals such as lithium, magnesium, and silicate and all degradation products that are known to affect osteogenic cell function.
…”
Section: Classification Of Nanocomposite Hydrogelsmentioning
confidence: 99%
“…On the other hand, the positively charged nanoclay edges compete with Ca 2+ for alginate junction sites. [ 41 ] Chemically crosslinked PNIPAAm chains bind to clay surfaces through hydrogen, ionic, and polar interactions. All these interactions lead to the formation of the 3D nanocomposite hydrogels with mutually interpenetrating and interacting inorganic and organic networks of ALG, PNIPAAm, and LAP with unique thermal and mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we prepared hyaluronan (HA) derivatives in which aminobisphosphonates were permanently attached to HA backbone through stable chemical bonds, thereby excluding possibility for the release of aminobisphosphonates as intact drugs [ 29 , 30 ]. It was also demonstrated that these HA-BP derivatives formed shear-thinning and self-healing hydrogels upon interaction with either hydrated metal ions such as Ca 2+ [ 31 ], Mg 2+ [ 32 ], Ag + [ 33 ], or nanoparticles of inorganic salts such as calcium phosphate [ 30 ], magnesium silicate [ 32 ], calcium sodium phosphosilicate (bioglass) [ 34 ], and clay [ 35 ].…”
Section: Resultsmentioning
confidence: 99%